No Honour in Honour Killing: Comparative Analysis of Indian Traditional Social Structure vis-à-vis Gender Violence. Issue 1 (June 2020) - Kaushal, Kaushambi
India is always proud of its democracy, secularism between and after so many years of Independence. However, ethos of marriage remains the same. Marriages tend to be a holy sacrament solemnized by families. In some of the cases, young innocent women are subjected to horrific and horrendous waves of massacring for choosing the life partner according to their wish and choice. Moreover, this choice makes the women vulnerable to the alleged supreme caste, religious group and old guards of the society. A killing in the name of honour inculcates torture and rejection of equalitarianism, which is a corner stone of the Indian Constitution. Furthermore, it manifests how the value of feudalism and patriarchy is rooted in our social system in some corner. The qualitative- and quantitative-based comparative analyses of the study would depict various perspectives of violence, its vulnerability and peril nature towards some of Indian Women. In this backdrop, it is difficult to state the precise number of Honour Killings because many cases go unreported. In some of the cases, the perpetrators go unpunished and the concept of the honour becomes justified in the eyes of societies. It is estimated by the United Nations Population Funds that 5, 000 women and girls are killed by their own family members. According to the recent report of National Crime Record Bureau, 356 cases of Honour Killing were reported along with 65 cases of culpable homicide in India. There are laws in Indian Penal Code for the Honour Killings; but it is just an antidote to such dishonourable practices. Law should be amended and made stringent towards it. It is manifested that a wide range of moderation is needed in order to effectively battle against patriarchal crimes and women's sovereignty in India. It is not out of the context to mention here that 'The Freedom of Belief doesn't mean Freedom to Kill. Everyone has right to live there life with dignity, grace and equality. A woman deserves respect with dignity. There is No Honour in Honour Killings'.